The Standard of Living of the Inhabitants of Royal Towns in Moravia during the Price Revolution (1540–1620) - Zaoral, Roman (Theatrum historiae, 2023)
Using the methodological approach formulated by Robert C. Allen in 2001, the study examines prices and wages in the 16th-century Czech lands, whence, unlike most other European countries, comparative data about real wages have not yet been published. The reason is evident: there is no published edition with data suitable for this type of research. Unlike Bohemia, data from Moravia collected by Jaroslav Novotný provide a better basis for real wage calculation. Novotný excerpted data from all Moravian archives and recorded them on about 50,000 price cards deposited in the Moravian Land Archives in Brno. In combination with data published in cyclostyled workbooks Ceny, mzdy a měna [Prices, Wages, and Currency] during the 1960s, it was possible to create a database for the welfare ratio of nominal wages to the consumer price index. The research focused on a comparison of living standards in three Moravian royal towns (Olomouc, Brno, and Znojmo) in the period of the price revolution (1540–1620) proving that the situation in Moravia was similar to that in other Central European towns (Cracow, Vienna): the unqualified labourers lived under borderline poverty status and their economic potential was slightly decreasing. Nevertheless, neither benefits to wages, which are not provable in historical sources, could be included in calculations, nor the possibility of replacing some commodities of the consumer basket with cheaper substitutes. On the other hand, the real wages of master craftsmen were increasing. The results evidence that Central Europe was a specific region of the Small Divergence (low prices – low wages), unlike North Western Europe, particularly Amsterdam, and London, where prices and wages were considerably growing. It was a consequence of the uneven distribution of South American precious metals in Europe which resulted in the Great Divergence (high prices – high wages) in England and the Netherlands. The relationship between money supply and the price level is examined using Fisher´s equation of exchange, which retrospectively confirms the validity of the ascertained tendencies of development.